Research on Design Method of Bionic Tooth Profile High-torque Synchronous Pulley - Shuai Mo; Lijuan Shi; Zongxiang Yue; Xiaolin Cao; Yunsheng Huang (Jixie chuandong)
Aiming at the influence of the tooth profile of the synchronous pulley on the bearing capacity of the pulley， a design method of a high-torque bionic tooth profile synchronous pulley is proposed. A simplified tangent curve is obtained from the bionic connection of the stretched triangle pattern of the trunk and the ground， which is used as the tooth profile of the bionic synchronous pulley， and a parameterized method for describing the tooth profile of the synchronous pulley is designed. The tangent curve is optimized by using the finite element embedded optimization module， and finally the parameters of the tangent curve with the minimum uniform stress of the teeth are obtained. The uniform stress distribution of the tooth roots of the bionic synchronous pulley and the conventional arc synchronous pulley is compared. The research shows that the proposed method can significantly reduce the uniform distribution stress of the synchronous pulley and reduce the root stress concentration. Compared with the arc toothed synchronous belt pulley， the bionic toothed profile belt has a more reasonable load distribution and higher bearing capacity.